2016
DOI: 10.1371/journal.pone.0147976
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Asthma Based on Nonlinear Analysis of Breathing Pattern

Abstract: Normal human breathing exhibits complex variability in both respiratory rhythm and volume. Analyzing such nonlinear fluctuations may provide clinically relevant information in patients with complex illnesses such as asthma. We compared the cycle-by-cycle fluctuations of inter-breath interval (IBI) and lung volume (LV) among healthy volunteers and patients with various types of asthma. Continuous respiratory datasets were collected from forty age-matched men including 10 healthy volunteers, 10 patients with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 57 publications
(109 reference statements)
6
41
1
1
Order By: Relevance
“…Detrended fluctuation analysis of inter-breath intervals in group of rats with variable mechanical ventilation demonstrates a linear correlation between the log(scale) and log(fluctuations) as shown in figure 1. This indicated that variable mechanical ventilation has a fractal-like dynamic similar to healthy individuals (Raoufy et al 2016). Similar fractal-like pattern of fluctuation was observed in tidal volume fluctuations in the variable mechanical ventilation group as expected (data not shown).…”
Section: Resultssupporting
confidence: 86%
“…Detrended fluctuation analysis of inter-breath intervals in group of rats with variable mechanical ventilation demonstrates a linear correlation between the log(scale) and log(fluctuations) as shown in figure 1. This indicated that variable mechanical ventilation has a fractal-like dynamic similar to healthy individuals (Raoufy et al 2016). Similar fractal-like pattern of fluctuation was observed in tidal volume fluctuations in the variable mechanical ventilation group as expected (data not shown).…”
Section: Resultssupporting
confidence: 86%
“…Analyzing such nonlinear fluctuations may not only improve traditional assessments in diagnosing the onset of illness, its severity and prognosis (1), but also could provide new insights into the different pathophysiological characteristics of respiratory diseases (2). In addition to studies described by Thamrin and colleagues (1), our recent report (2) showed that both respiratory rhythm and volume fluctuate continuously under a delicate equilibrium to maintain adaptability to external or internal stimuli. These fluctuations showed decreased long-range correlation, increased regularity and reduced sensitivity to initial conditions in patients with asthma, particularly in uncontrolled state.…”
Section: Letter To Editormentioning
confidence: 91%
“…A section of the article described previous studies that characterized the complex behavior of the lung in respiratory diseases using nonlinear analysis of the fluctuations of physiologic variables over time. Chronic lung diseases have variable clinical symptoms and represent complex behavior which may be associated with a shift in dynamics of respiratory system toward either too regular or too irregular (2). Analyzing such nonlinear fluctuations may not only improve traditional assessments in diagnosing the onset of illness, its severity and prognosis (1), but also could provide new insights into the different pathophysiological characteristics of respiratory diseases (2).…”
Section: Letter To Editormentioning
confidence: 99%
See 2 more Smart Citations